PENGENDALIAN KOLESTEROL DARAH DAN PENYIAPAN MENU HARIAN RENDAH KALORI DI DESA PEDAWA BULELENG - Wiryanthini, I.A.D.; Surudarma, I.W.; Sutadarma, I.W.G.; Wihandani, D.M. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana Mengabdi, 2023)
Uncontrolled blood cholesterol can cause health problems, one of which is stroke. An increase in blood cholesterol is influenced by a person's lifestyle, such as a high-calorie and fat diet and lack of exercise. The implementation of this service aims to improve public health status by increasing information about the importance of measuring daily diet and blood cholesterol. Examination of blood cholesterol levels is only done once in the form of a prevalence study. Respondents were 47 residents of Pedawa Village who visited Wantilan Village in Pedawa, the prevalence of respondents with hypercholesterolemia was 53.2%. Therefore, outreach and education activities are needed to increase public knowledge about cholesterol and diseases caused by high blood cholesterol levels in order to improve public health. Keywords: Pedawa Village, hypercholesterolemia, blood cholesterol, daily menu, stroke disease